Impenhorabilidade do salário: um estudo de caso múltiplo sobre os processos decisórios no Superior Tribunal de Justiça. - Silva, Renan Francelino da (2024)
What circumstances influenced the bodies of the Superior Court of Justice (STJ) to decide differently on the issue of salary unseizability? The legal base for unseizability of salary is provided in article 833, section IV, of the Civil Procedure Code. However, the literature argues that the Brazilian Courts have been giving a different interpretation to such norm. To answer the research question, an empirical-qualitative research was developed, through a multiple or comparative case study. A set of hypotheses elaborated based on the categories presented by two formal explanatory models of judicial behavior was tested – legalistic and attitudinal. A database was created with 04 (four) representative rulings on the matter of salary unseizability, in the period 2016-2023, through the Jurisprudence portal of the Court. The empirical models presented present elements of the attitudinal model: the decision-making pattern is defined by subjectivity determined based on open constitutional principles and norms so that the decision on the debtor's salary penalty is political, not technical.